2004
DOI: 10.1038/sj.ejhg.5201285
|View full text |Cite
|
Sign up to set email alerts
|

Fcγ receptor IIA genotype and susceptibility to P. aeruginosa infection in patients with cystic fibrosis

Abstract: It has been suggested that genes other than CFTR could modulate the severity of lung disease in cystic fibrosis (CF). Neutrophil Fcc receptor II (FccRII) is involved in host defense against microorganisms and in inflammatory response. We evaluated the association between genetic variability of this gene and both airway infection with Pseudomonas aeruginosa and severity of lung disease in patients with CF. We studied 167 Italian unrelated patients with CF and 50 control subjects. The distribution of FccRIIA gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 32 publications
(18 reference statements)
0
12
1
Order By: Relevance
“…As expected, CD32- and CD25-null mice showed deficiencies in myeloid and lymphoid development (3235). In humans, allelic variants of FCGR2A have been associated with susceptibility to systemic lupus erythematosus and to bacterial infections in certain populations (3638). These findings are attributed to differential function of phagocytes bearing the particular polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, CD32- and CD25-null mice showed deficiencies in myeloid and lymphoid development (3235). In humans, allelic variants of FCGR2A have been associated with susceptibility to systemic lupus erythematosus and to bacterial infections in certain populations (3638). These findings are attributed to differential function of phagocytes bearing the particular polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies have examined mostly immune or inflammatory genes, including ACE [19,20], ADRβ2 [2023], ATB 0 [24], CAPN10 [25], ClCN2 [26], DEFβ4 [27], ENaC [28], FcβRII [29], GCLC [30], GSTM1 [20,31–35], GSTM3 [34], GSTP1 [20,3335], GSTT1 [34], HFE [36,37], HLA-I [38], HLA-II [3841], HLA-III [38], HSP70 [39], IFN-γ [19], IL1-β [39], IL6 [25], IL10 [19,20,42], IL18 [25], KCNJ11 [25], MBL2 [20,4352,53 •• ], MIF [54], NOS1 [5557], NOS3 [20,58], MASP-2 [48,51], PPARβ [25], SERPINA1 [20,59–67], SERPINA3 [68], SFTPA1 [50], SFTPA2 [50], TLR4 [69], TGFB1 [19,20,52,53 ββ ,67,7072 •• ,73 •• ], TNFα [19,20,25,32,52,7476], TNFα -receptor [28], and TNFβ [39]. …”
Section: Candidate Gene Studiesmentioning
confidence: 99%
“…To date several gene–gene interactions have been reported between CFTR and modifier genes, including GCLC [30], MBL2 [49,50], FCγRII [29], NOS1 [55], and TGFβ1 [19,73 •• ]. Most of these reported gene– CFTR interactions demonstrate the presence of or increased variant polymorphism effects in the context of ΔF508 or other severe mutation homozygosity, excepting the GCLC – CFTR interaction and the TGFB1 – CFTR interaction as reported by Bremer et al Other reported gene–gene interactions in CF include MBL2 – TGFB1 [53 •• ], TNF •-8.1 ancestral MHC genotype [75], and GSTM1 – GSTP1 [35].…”
Section: Interactionsmentioning
confidence: 99%
“…Little is known about factors which could protect the CF host against chronic infection. The patient's genetic background may play a role [7][8][9], or the ability to produce opsonophagocytic antibodies against PA [10].…”
Section: Introductionmentioning
confidence: 99%